A study on organizational factors that affect employees' performance at private clinics in Sungai Petani / Nur Daiey An Abd Khalid and Nur Hidayah Mohamad Jamil - Abd Khalid, Nur Daiey An; Mohamad Jamil, Nur Hidayah (2018)
This chapter focuses on the background of the study which is the organizational factors that affect employees' performance at private clinics in Sungai Petani. The presentation of this chapter begins with the background of the research, statement of problem, research questions, research objectives, scope of the study, significance of the study and the definitions of terms and concepts used in this study.